FISH Detection of PML-RARA Fusion in ins(15;17) Acute Promyelocytic Leukaemia Depends on Probe Size. (28th March 2013) - Campbell, Lynda J.; Oei, Paul; Brookwell, Ross; Shortt, Jake; Eaddy, Nicola; Ng, Ashley; Chew, Edward; Browett, Peter
Abstract : The diagnosis of acute promyelocytic leukaemia (APL) is usually confirmed by cytogenetics showing the characteristic t(15;17), but a minority of patients have a masked PML/RARA fusion. We report ten patients with APL and no evidence of the t(15;17), in whom the insertion of RARA into PML could not be demonstrated by initial FISH studies using a standard dual fusion probe but was readily identified using smaller probes. Given the need for rapid diagnosis of APL, it is important to be aware of the false negative rate for large PML/RARA FISH probes in the setting of masked rearrangements.